Multigenerational and gender-symmetric transmission of migration behaviors in historical Quebec - Marielle Côté-Gendreau (Proceedings of the National Academy of Sciences, 2026)
Migration decisions are embedded in social and family trajectories that escape traditional data sources, which tend to observe individuals in isolation. Genealogical microdata now make it possible to trace these dynamics over long time horizons. This paper documents how prior generations’ migration histories shape future internal migration behavior, leveraging rich historical microdata spanning over two centuries and multiple generations at the scale of an entire population (Quebec, Canada; 1621–1861). As the cultural norm preserved women’s maiden names throughout the life course, genealogies could be assembled as exhaustively for women as for men. Using residential trajectories reconstructed from these linked vital data, the study shows that the mobility of married couples depends on both spouses’ parents’ and grandparents’ migration histories. Descendants of migratory people are substantially more likely than their peers from sedentary families to migrate themselves, the effect of the grandparental generation being about half that of the parental generation. These effects compound such that couples with multiple migratory ascendants are even more likely to migrate. Moreover, husbands’ and wives’ migration backgrounds are equally predictive of their joint mobility decisions, suggesting a substantial role of women in shaping couples’ mobility and challenging the conventional assumption that migration decisions were historically made by men. These results reveal deep family history as an underexplored axis of migrant selection. The long-lasting influence of family should be integrated in migration theories.